Engaging the Efficacy of Nigerian Popular Gospel Music and Pentecostalism for Nigerian Church Growth - Akande, Sunday Olufemi (NIU Journal of Humanities; Vol. 8 Núm. 4 (2023): NIU Journal of Humanities, Vol. 8 No. 4, December 2023, 2023)
In the 1970s and 1980s there was the emergence of Pentecostalism that gave rise to the establishment of many Churches in Nigeria. Among the churches that were established are ; Deeper Life Bible Church, New Living Faith Church also known as Winners Chapel, The Redeemed Christian Church of God, Gospel Faith Mission and many others. The rate at which other churches are springing up and the founding of many other branches is alarming till date. The Proliferation of churches led to the existence of churches everywhere in Nigerian society. However, the numeric increase or proliferation of Churches in Nigeria is not attributed only to the mode of worship, prayers and to signs and miracles introduced to Churches through Pentecostalism but also influenced by music. The value of music should never be lost sight of in worship. The relationship between music and Pentecostalism cannot be undermined as music cannot be separated from worship. This paper examines the efficacy of contributions of music in genre, form and performance practice in Church growth, specifically in Nigeria. This research reviewed the history and explosion of Pentecostalism in Nigeria. The materials used in this research were sourced from books, journals, magazines and Internet. Historical research design was used for this study. This paper concludes that the mystic effect and intrinsic value of music affects church growth and should be considered as a viable tool together with Pentecostalism for Church growth in Nigeria. Keywords: Efficacy, Music, Pentecostalism, Church Growth